2016
DOI: 10.2147/ppa.s114172
|View full text |Cite
|
Sign up to set email alerts
|

Physician and patient benefit–risk preferences from two randomized long-acting injectable antipsychotic trials

Abstract: PurposeTo quantify clinical trial participants’ and investigators’ judgments with respect to the relative importance of efficacy and safety attributes of antipsychotic treatments for schizophrenia, and to assess the impact of formulation and adherence.MethodsDiscrete-choice experiment surveys were completed by patients with schizophrenia and physician investigators participating in two phase-3 clinical trials of paliperidone palmitate 3-month long-acting injectable (LAI) antipsychotic. Respondents were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…The finding in this study that reduced disease symptoms and functional impacts were most important, whereas reduced risk of treatment side effects, specifically weight gain, sexual problems, fatigue, and restlessness, were least important, is consistent with that from a previous stated preference survey in an older group of individuals with schizophrenia (mean age =41 years) that used a discrete choice experiment (DCE) methodology. 35 In addition, consistent with the finding in this study that people with LAI experience more often preferred LAI over oral medication, the patients in the DCE study, who were participants in a LAI trial, had a higher preference for a LAI over oral medication. 35 Another study, involving qualitative interviews, also found that preference was higher for LAI among those with LAI experience.…”
Section: Discussionsupporting
confidence: 81%
“…The finding in this study that reduced disease symptoms and functional impacts were most important, whereas reduced risk of treatment side effects, specifically weight gain, sexual problems, fatigue, and restlessness, were least important, is consistent with that from a previous stated preference survey in an older group of individuals with schizophrenia (mean age =41 years) that used a discrete choice experiment (DCE) methodology. 35 In addition, consistent with the finding in this study that people with LAI experience more often preferred LAI over oral medication, the patients in the DCE study, who were participants in a LAI trial, had a higher preference for a LAI over oral medication. 35 Another study, involving qualitative interviews, also found that preference was higher for LAI among those with LAI experience.…”
Section: Discussionsupporting
confidence: 81%
“… 60 The second RCT aimed to demonstrate non-inferiority of PP3M compared with PP1M in terms of relapse rates, changes in Positive and Negative Syndrome Scale (PANSS) scores, Clinical Global Impression-Severity (CGI-S) score and Personal and Social Performance (PSP) score. 61 Savitz et al, 62 Katz et al, 63 Chirila et al, 64 and Gopal et al 65 studied outcome measures within the samples or sub-samples of the 2 previously described RCTs. In details, Savitz et al 62 analyzed data derived from the previously mentioned non-inferiority RCT comparing PP3M with PP1M treatment; to investigate symptomatic and functional remission in the DB phase of this RCT, Katz et al 63 investigated native English-speaking trial participants’ and English-speaking investigators’ judgments about paliperidone formulations and adherence; Chirila et al 64 compared occupational status and health care resource use between treatment groups (PP3M vs placebo and PP3M vs PP1M), using data from the whole samples of the 2 RCTs and Gopal et al 65 evaluated caregiver burden in the 2 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“… 61 Savitz et al, 62 Katz et al, 63 Chirila et al, 64 and Gopal et al 65 studied outcome measures within the samples or sub-samples of the 2 previously described RCTs. In details, Savitz et al 62 analyzed data derived from the previously mentioned non-inferiority RCT comparing PP3M with PP1M treatment; to investigate symptomatic and functional remission in the DB phase of this RCT, Katz et al 63 investigated native English-speaking trial participants’ and English-speaking investigators’ judgments about paliperidone formulations and adherence; Chirila et al 64 compared occupational status and health care resource use between treatment groups (PP3M vs placebo and PP3M vs PP1M), using data from the whole samples of the 2 RCTs and Gopal et al 65 evaluated caregiver burden in the 2 RCTs. Weiden et al 66 made a post-hoc analysis comparing median time to relapse across the treatment withdrawal arms of 3 different RCTs (Kramer et al, 67 Hough et al, 68 and Berwaerts et al 60 ), which compares the 3 formulations of paliperidone with placebo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An American study has surveyed doctors and service users by asking them to rate the importance of efficacy, safety, and formulation for monthly, 3‐monthly, or oral administration. Both doctors and service users pointed toward the reduction of positive symptoms as the most important target, and both groups preferred LAIs over oral treatment . An Australian study has rated patient satisfaction with PP3M among service users as well as psychiatrists based on questionnaires.…”
Section: Purposementioning
confidence: 99%